The Degeneration of Corruption at the Zenith and how to Delimit it for the Upskill in the Stem Education - Ann Ngozi Ugobueze (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: Corruption in the education sector poses a serious threat to academic integrity, the credibility of institutions, and the overall quality of education. It undermines public trust, devalues merit, and weakens the foundation of learning, particularly in STEM education where precision and ethical standards are paramount. Objective: This study aims to examine the negative effects of corruption in education and explore effective strategies to mitigate its impact in order to improve educational standards and foster integrity, especially within STEM disciplines. Method: A qualitative descriptive approach is employed, involving literature reviews and observational analysis of documented corruption cases in the education sector. Data were collected through document analysis, interviews with education stakeholders, and a review of institutional policies related to anti-corruption measures. Result: The findings reveal that corruption in education takes various forms, such as academic fraud, grade manipulation, admissions bribery, and dishonest examination practices. These malpractices contribute to the deterioration of educational quality, the erosion of public trust in educational institutions, and the loss of core ethical values in academic environments. Conclusion: To combat the degeneration caused by corruption, systemic educational reforms are essential. These should include increased transparency, stricter regulatory enforcement, and comprehensive anti-corruption policies. Moreover, fostering integrity and ethical values from early education levels is vital in cultivating a corruption-resistant academic culture. Contribution: This study provides valuable insights and recommendations for educators, policymakers, and society at large in designing strategies and policies to combat corruption in education. It contributes to the promotion of a credible, ethical, and high-quality educational system, particularly in STEM fields, where integrity and excellence are foundational.